Trends and issues in distance education : international perspectives - Visser, Lya; Visser, Yusra Laila; Amirault, Ray J.; Simonson, Michael R. (Perspectives in instructional technology and distance learning., 2012)
Over the last decade, the field of distance education (and e-learning) has substantially strengthened and assumed a more international scope. There has been an impressive growth in the conceptual, empirical and experiential foundations of the field. Trends and Issues in Distance Education: International Perspectives (2nd Ed) captures a representative snapshot of the breadth of current global trends and issues in distance education theory, research, and practice. Through 21 chapters (from over 30 international authors), the book documents new developments in distance education scholarship and practice, presenting a diverse set of viewpoints on the trends and issues affecting this increasingly central discipline.The book is for researchers, practitioners, and students. Chapters speak to the many creative ways in which distance education addresses learning and human development needs around the world. They focus on distance education in dissimilar settings that extend beyond the limitations of the dominating paradigms of the highly developed economies. Contributing authors touch upon conceptual as well as practical issues. They critically reflect on both large- and small-scale distance education initiatives, discussing the use of everything from the most advanced technologies (e.g., 3-D computing) to the most rudimentary technologies (e.g., wind-up radios).